Peran Guru PAI Dalam Internalisasi Nilai - Nilai Moderasi Beragama Di SMP Qur’an Darul Fattah Bandar Lampung - Asep Bambang Susanto (Sekolah Tinggi Ilmu Tarbiyah Darul Fattah, 2023)
Indonesia is a country of rich and diverse diversity. When everyone understands their role, various conflicts arise. School is a place where the younger generation spends their time. The role of PAI teachers has a very important place so that the value of moderation in various religions is conveyed appropriately to students. The aim of this research is to identify PAI teacher traits in the internalization of religious moderation values ​​and reveal strategies, methods, supporting and inhibiting factors in the internalization of religious moderation values. The method used is descriptive qualitative type of case study. Data collection_using the observation method. Interviews and documentation. Then, data analysis includes data collection, data reduction, data presentation, drawing conclusions, and verification. The results of the research show that the strategies used by PAI teachers in internalizing the values ​​of religious moderation are example, applying discipline, tolerance, giving advice to students. PAI teacher methods include providing understanding, monitoring, and efforts to encourage students to appreciate the values ​​of religious moderation. Supporting factors include the existence of a moral program, Islamic boarding school curriculum, character building, OSIS activities, teacher and guardian studies, general guidebooks and mutaba'ah evaluation books. One of the inhibiting factors is the rapid progress of technology which influences the way of thinking and attitudes of students.